Interrogating the global application of e-certification of seafarers - Margie Mendoza Mataac; Michael Ekow Manuel; Anne Pazaver (Digital Transformation and Society)
Purpose – Amidst the ongoing digital transformation in the maritime industry, this study aims to interrogate the application of electronic certification (e-certification) to seafarers globally. Design/methodology/approach – Data and methodological triangulation were used in the study. This included a scoping review to analyze the components of effective e-certificates; document analysis to evaluate the nature and functions of the international legal framework of seafarers’ e-certification and thematic and statistical analyses of responses from survey questionnaires and interviews to examine the merits, demerits and challenges to global implementation of seafarers’ e-certification. A modified Unified Theory of Acceptance and Use of Technology (UTAUT) model was used to determine the stakeholders’ usage behavior regarding seafarers’ e-certification. Findings – The results revealed several merits associated with the implementation of seafarers’ e-certificates, outweighing the presence of certain drawbacks. It also identified various challenges to global application along with potential solutions. Despite the strong industry support for the entire replacement of seafarers’ traditional printed certificates with e-certificates, the study concludes that the coexistence of both formats will persist until crucial challenges are effectively addressed. The International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW), 1978, as amended, along with the relevant International Maritime Organization (IMO) guidelines, functions as the international legal framework for the effective global application of electronic certification for seafarers. Originality/value – The study addresses a significant aspect of the contemporary digital transformation of seafarers’ certification under the STCW Convention, 1978, as amended.